Epidemiology of skydiving-related deaths and injuries: A 10-years prospective study of 6.2 million jumps between 2010 and 2019 in France. Issue 5 (May 2021) - Fer, Caroline; Guiavarch, Michel; Edouard, Pascal
Abstract: Objectives: To analyse the data on skydiving deaths and injuries collected prospectively by the French Parachuting Federation (FFP) between 2010 and 2019. Design: Prospective cohort study. Methods: Data on number of skydiving deaths and injuries were collected prospectively between January 2010 and December 2019, among all skydivers licensed to the FFP, via a standardised report form that included the skydiver's sex and level of experience (classified as tandem, student, or experienced), deaths, injuries, and injury location. The number of licensees, jumps, skydiving deaths and injuries were analysed descriptively and expressed as rates per 100, 000 jumps and per 1000 skydivers with 95% confidence intervals (95%CI). Results: Among the almost 6.2 million jumps performed by 519, 620 skydivers over 10 years between 2010 and 2019, 35 deaths and 3015 injuries were reported, corresponding to 0.57 deaths (95%CI 0.38 to 0.75) and 49 injuries (95%CI 47.0 to 50.1) per 100, 000 jumps. Male skydivers had a five times higher deaths rate than women (RR = 4.8, 95%CI 1.5 to 15.6). There was no death in tandem skydivers. Student skydivers had a six times higher risk of injuries than experienced skydivers (RR = 6.1, 95%CI 5.7 to 6.6) and tandem skydivers had a significant lower risk of injuries than experienced skydivers (RR = 0.07, 95%CI 0.06 to 0.08). 83.3% of the injuries occurred during the landing phase and 64.3% concerned the lower limb. Conclusions: This large survey shows that the highest risk of death concerned experienced and male skydivers, and the highest risk of injuries concerned student skydivers. It also shows the safety of tandem skydiving. These results can be of help to develop skydiving-related deaths and injuries risk reduction strategies, and thus improve the global skydiving safety and the skydivers' health.